Revising Reason: Creating an Emotionally Engaged Legal Academia. Issue 1 (June 2020) - Mishra, Pragya
In this article, my focus is to examine where, when, how, and why that most animating psychological concept—emotion—influences law and legal academia. In particular, this article will consider how law considers reason its supreme driving force, representing rationality and enlightenment and prizes the rigid, analytical, unemotional ability to 'think like a lawyer' whilst modern neuroscientific and philosophical findings no longer consider emotions as an antithesis of reason but rather deeply intertwined with cognition. Thus, briefly illustrating some of the inconsistencies, contradictions, and incoherence among legal education's theories of emotion, as seen through law and emotions scholarship, this article argues that emotions can and should be the driver for a more holistic form of legal education, one in which emotions and well-being are integral within the curriculum itself, rather than occasional adjuncts.